New Travelling-Wave Solutions for Dodd-Bullough Equation - Guicheng Shen; Yunchuan Sun; Yongping Xiong (Journal of Applied Mathematics)
A new method, which assumes ϕ' with a function form of f(eϕ), is applied to solve the Dodd-Bullough equation ϕuv=eϕ-e-2ϕ through travelling-wave transformation. A new family of explicit travelling wave solutions is derived. The proposed method works efficiently to be applied to solve other forms of Dodd-Bullough equations.